Prison in Russian Literature: Notes from the House of the Dead by Fyodor Mikhailovich Dostoevsky as a Model - Abboudi, Amal; ailane, omar (El Omda in Linguistics and Discourse Analysis, 2023)
Abstrect The prison literature is about an experience and sufferance in the prison; many authorswrite about their experiences either inside or outside the prison. Numerous novels, stories and poetic works use the prison as their main theme. One of the most famous literary works is “The House of Dead” by the Russian writer Dostoevsky. The House of dead in this novel is the forced labour prison in Siberia. The hero of this novel “PetrovichGoryanchikov” speaks in details about the hard life in the prison. This study follows the thematic analysis attempting to represent the main negative as well as the positive features in this literary work and how Dostoevsky dealt with his experience in the prison